Black Duck Brook graveyard with the old two-room schoolhouse in background - Ledrew, Karen (1988)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « A Folklore Field Trip to Black Duck Brook on March 12-March 16, 1988: An account of experiences ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "A Folklore Field Trip to Black Duck Brook on March 12-March 16, 1988: An account of experiences".